2016
DOI: 10.1097/ccm.0000000000001563
|View full text |Cite
|
Sign up to set email alerts
|

Alda-1 Attenuates Lung Ischemia-Reperfusion Injury by Reducing 4-Hydroxy-2-Nonenal in Alveolar Epithelial Cells

Abstract: Our study indicates that the accumulation of 4-hydroxy-2-nonenal plays an important role in lung ischemia-reperfusion injury. Alda-1 pretreatment can attenuate lung ischemia-reperfusion injury, possibly through the activation of aldehyde dehydrogenase-2, which in turn removes 4-hydroxy-2-nonenal in human pulmonary alveolar epithelial cells. Alda-1 pretreatment has clinical implications to protect lungs during cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Our findings were consistent with the reported anti-inflammatory property of Alda-1 [17,29]. In a mouse model of lung I/R, the TNF-α and IL-1β were significantly reversed from the I/R-induced elevation to levels similar to that of control groups [17]. Similarly, in a rat model of myocardial infarction, the number of TNF-α-positive cells was significantly decreased by Alda-1 treatment [29].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings were consistent with the reported anti-inflammatory property of Alda-1 [17,29]. In a mouse model of lung I/R, the TNF-α and IL-1β were significantly reversed from the I/R-induced elevation to levels similar to that of control groups [17]. Similarly, in a rat model of myocardial infarction, the number of TNF-α-positive cells was significantly decreased by Alda-1 treatment [29].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our expectation, the serum levels of TNF-α, IL-1β and IL-6 were significantly suppressed by Alda-1 treatment, paralleling the remarkably decreased morphological damage in the lung and intestine. Our findings were consistent with the reported anti-inflammatory property of Alda-1 [17,29]. In a mouse model of lung I/R, the TNF-α and IL-1β were significantly reversed from the I/R-induced elevation to levels similar to that of control groups [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Figure 5A, both MCP-1 and ICAM-1 protein were increased after inhibiting ALDH2 activity. To determine the exact effect of ALDH2, we used Alda-1, a novel small molecule which can activate catalysis for both wild-type ALDH2 (ALDH2*1) and ALDH2*2 [25, 26], to stimulate ALDH2 activity. We demonstrated that 20μM Alda-1 increased ALDH2 activity approximately by 80% with no effect from the solvent DMSO (Figure S2B).…”
Section: Resultsmentioning
confidence: 99%